Ejaculatory abstinence in semen analysis: does it make any sense? - Shah Dupesh; Natarajan Pandiyan; Radha Pandiyan; Jeeva Kartheeswaran; Bhaskar Prakash (SAGE Publishing, 2020)
Background: The precise effect of ejaculatory abstinence on semen parameters is highly debatable, especially among subfertile men. Previous studies on effect of abstinence time on different semen parameters have reported controversial results. The aim of this study was to retrospectively assess the variance of semen parameters with different periods of ejaculatory abstinence among both a population of normozoospermic ( n  = 1621) and oligozoospermic ( n  = 416) Tamil men, presenting to a fertility clinic for an infertility evaluation ( N  = 2037). Materials and Methods: A retrospective analysis of 2037 semen analysis reports involved grouping patients based on their ejaculatory abstinence, that is, <24 h, 1 to 2 days, 3 to 7 days, 8 to 15 days, 16 to 30 days, and >30 days. All semen parameters were assessed as per the World Health Organization (WHO, 2010) recommended guidelines. The unpaired two-tailed t -test and Welch's analysis of variance (ANOVA) combined with Games-Howell post hoc test were used for statistical analysis. A p value <0.05 was considered to be statistically significant. Result: A retrospective analysis of data ( N  = 2037) identified no statistically significant differences in semen parameters of sperm concentration, percentage of progressively motile sperm, and normal sperm morphology in both normozoospermic and oligozoospermic individuals across different groups of abstinence. Semen volume was the only parameter that showed a statistically significant difference in both groups ( p  < 0.0001). In both normozoospermic and oligozoospermic men, the group with <24 h abstinence had the highest mean percentage of progressively motile sperm and normal sperm morphology. Conclusion: The findings of this study suggest that ejaculatory abstinence may be highly arbitrary, and the recommendation of a strict 2- to 7-day abstinence per the WHO may be liberalized. In both normozoospermic and oligozoospermic men, semen parameters associated with an abstinence of <24 h were found to be noninferior as compared to longer ejaculatory abstinence intervals. These findings support in eliminating conservative recommendations as far as abstinence is concerned and suggest that patients may be asked to collect a semen sample on the day they present for an infertility evaluation, regardless of abstinence.